2016
DOI: 10.3102/0013189x16683408
|View full text |Cite
|
Sign up to set email alerts
|

Examining Racial Bias in Education

Abstract: In this article we argue that social-psychological research on implicit racial associations—relatively unconscious associations based on race—is a fruitful area to explore for a greater understanding of how racial bias affects children in schools. We highlight the key insights of research on implicit racial associations and their implications for education. Further, we identify areas for research on implicit racial associations in education, calling for collaboration between scholars of racial inequality in ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 36 publications
0
71
0
Order By: Relevance
“…In the transformative view, equity means challenging oppression, including racism and classism (Dixson and Rousseau 2005). This perspective suggests that oppression is perpetuated through structural practices, such as racial disproportionality in discipline (Anyon et al 2016) or course placement , as well as educators' implicit biases and expectations (Warikoo et al 2016). This view also assumes intersectionality: individuals possess multiple social identities, and an understanding of oppression must consider the interactions among the dynamics of race, national origin, class, gender, language, ability, and other constructions (Crenshaw 1991;Solórzano and Bernal 2001).…”
Section: February 2019 177mentioning
confidence: 99%
“…In the transformative view, equity means challenging oppression, including racism and classism (Dixson and Rousseau 2005). This perspective suggests that oppression is perpetuated through structural practices, such as racial disproportionality in discipline (Anyon et al 2016) or course placement , as well as educators' implicit biases and expectations (Warikoo et al 2016). This view also assumes intersectionality: individuals possess multiple social identities, and an understanding of oppression must consider the interactions among the dynamics of race, national origin, class, gender, language, ability, and other constructions (Crenshaw 1991;Solórzano and Bernal 2001).…”
Section: February 2019 177mentioning
confidence: 99%
“…Following DiMaggio 69 , Zerubavel 70 and others, cultural sociologists are building a bridge towards cognitive science by incorporating the DPM of cognition 71 , embodiment 72 , networks 73 , implicit bias 74 and emotions into cultural sociology. Shepherd 67 in particular has considered the impact of symbols and media, place, situation and networks in IAT research.…”
Section: Discussion and Future Agendamentioning
confidence: 99%
“…Conversely, our results indicated that migrant, limited English proficient, and Hispanic students are underrepresented in the GAA. Even in cases of underrepresentation, implicit associations held by teachers and staff can contribute to racial inequality via racial bias (Warikoo, Sinclair, Fei, & Jacoby-Senghor, 2016). Perhaps educators are less equipped to detect cognitive disabilities in migrant, limited English proficient, and Hispanic populations due to language barriers or other cultural differences.…”
Section: Primary Language/culturementioning
confidence: 99%